2015
DOI: 10.1038/ncomms6998
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bioimaging with fluorinated nanoparticles using breathable liquids

Abstract: Fluorocarbons are lipophobic and non-polar molecules that exhibit remarkable bio-compatibility, with applications in liquid ventilation and synthetic blood. The unique properties of these compounds have also enabled mass spectrometry imaging of tissues where the fluorocarbons act as a Teflon-like coating for nanostructured surfaces to assist in desorption/ionization. Here we report fluorinated gold nanoparticles (f-AuNPs) designed to facilitate nanostructure imaging mass spectrometry. Irradiation of f-AuNPs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 43 publications
0
57
0
Order By: Relevance
“… 18 , 20 , 23 However, these techniques may restrict detection of other classes of analytes compared to traditional matrixes, 24 frequently due to their affinity for specific classes of molecules 21 , 22 , 25 or fragmentation of higher molecular weight analytes. 26 , 27 Moreover, few of these approaches have been applied to the characterization of FFAs by MSI. 21 , 22 Time-of-flight (TOF)-SIMS is commonly utilized for FFA imaging in tissue sections but typically fragments large molecular ions.…”
mentioning
confidence: 99%
“… 18 , 20 , 23 However, these techniques may restrict detection of other classes of analytes compared to traditional matrixes, 24 frequently due to their affinity for specific classes of molecules 21 , 22 , 25 or fragmentation of higher molecular weight analytes. 26 , 27 Moreover, few of these approaches have been applied to the characterization of FFAs by MSI. 21 , 22 Time-of-flight (TOF)-SIMS is commonly utilized for FFA imaging in tissue sections but typically fragments large molecular ions.…”
mentioning
confidence: 99%
“…3840 As an example, AuNPs functionalized with perfluoroalkane thiol provided higher LDI-MS efficiency than citrate-stabilized AuNPs. 41 The surface of MoS 2 nanoflakes can be also modified with thiol derivatives through the coordination of thiol group to their defect sites or physisorption. 42,43 This surface modification strategy has been extensively employed for the cancer therapy and antibacterial application by using MoS 2 nanoflakes.…”
Section: Resultsmentioning
confidence: 99%
“…A tentative explanation for the underlying mechanism may be found in analogy to a recent study where perfluoroalkylated gold nanoparticles were used as a decomposing matrix to softly launch small biomolecules: a nanosecond UV laser pulse detached the ligands from the gold particles and provided an expanding perfluorinated matrix to launch the analyte biomolecules. 41 Here we propose that a similar mechanism may also be at work, however with the analyte particles providing their own matrix and the nanosecond laser pulse being replaced by millisecond laser heating. Earlier studies using microfocus laser sources showed that at laser intensities of 3 MW cm −2 thin layers of dye molecules could be heated to about 1000 K and evaporated intactly.…”
Section: Discussionmentioning
confidence: 96%